Statistical Assessment of The Implementation of Socio-Economic Development Strategies of The Republic of Uzbekistan in the Context of Digital Transformation - B. A. Begalov; I. E. Zhukovskaya (Статистика и экономика)
Purpose of the study. The main purpose of the article is to conduct a statistical assessment of the implementation of strategies for the socio-economic development of the Republic of Uzbekistan using an innovative methodology based on the use of digital technological solutions.Materials and methods. In the course of writing this article, the authors used the methods of system analysis, synthesis, statistical sampling and grouping, induction, deduction, methods of working with computer networks and digital platforms, special methods and tools necessary to optimize the work of the portal of the State Committee of the Republic of Uzbekistan on Statistics, as well as when working on this article, methods of working with digital technologies, specialized software products, web services were reflected.Results. The authors present the main technological approaches to conducting a statistical assessment of the activities of industries and spheres of the national economy of the Republic of Uzbekistan based on the use of digital mechanisms. New scientific approaches to the integration of statistical activities with other objects of the national economy in the context of digital transformation are proposed, the main directions for organizing the interaction of the statistical industry with economic objects within the framework of the National Program “Digital Uzbekistan – 2030” are identified. It is shown that in the modern period in the Republic of Uzbekistan a whole range of government decisions has been adopted on the comprehensive development of the country’s economic system based on the use of digital technologies. In addition, the article proves that the development of digital infrastructure is one of the determining conditions for increasing the competitiveness of the state on the world stage. At the same time, digital transformation contributes to the development of new methodological solutions for assessing the functioning of industries and spheres of the national economy. Scientific studies conducted by the authors state that due to the use of advanced information and digital technologies, innovative mechanisms for collecting and processing information flows, the statistical assessment of the implementation of a whole range of strategies for the development of the socio-economic complex is more open and transparent, which in turn allows you to make competent manage-ment decisions for the effective development of industries and areas of the national economy.Conclusion. This paper shows that the development and widespread use of digital technologies in all sectors of the economy and spheres of society today is a global trend in world development. The authors also state that the use of digital technological solutions is crucial for improving the living standards of citizens and the competitiveness of the national economy, expanding the possibilities of its integration into the global economic system, and increasing the efficiency of all levels of government. In turn, a statistical assessment of the results of the implementa-tion of the main provisions of the republican strategies for socio-economic development in the context of the formation of a digital economy shows that innovative approaches, developed and implemented information systems, web services and advanced technological solutions are fundamental elements for organizing an effective work on the processing of statistical information and the adoption of managerial decisions on the organization of the effective functioning of industries and spheres of the national economy.